Mobile Location-Based Gaming as Driver for Location-Based Services (LBS) - Exemplified by Mobile Hunters (Informatica, 2025)
Mobile Location-Based Gaming as Driver for Location-Based Services (LBS) - Exemplified by Mobile Hunters